Procamallanus (Procamallanus) spp. (Nematoda: Camallanidae) in fishes of the Okavango River, Botswana, including the description of P. (P.) pseudolaeviconchus n. sp. parasitic in Clarias spp. (Clariidae) from Botswana and Egypt - Moravec, František; Van As, Liesl L (Systematic parasitology, 2015)
Parasitological dissections of fishes from the Okavango River, Botswana, revealed the presence of nematodes of the subgenus Procamallanus (Procamallanus) Baylis, 1923 in five fish species belonging to three different families. Based on light and scanning electron microscopical examinations, they proved to represent one previously known and one new species, i.e. P. (P.) laeviconchus (Wedl, 1861) from Synodontis nigromaculatus Boulenger, S. thamalakanensis Fowler (new host) (both Mochokidae) and Schilbe intermedius Rüppel (new host) (Schilbeidae), and P. (P.) pseudolaeviconchus n. sp. from Clarias stappersi Boulenger and C. theodorae Weber (both Clariidae). Specimens of the new species previously collected from Clarias gariepinus (Burchell) (type-host) in Egypt were also examined. Both of these nematode species are very similar, differing from each other mainly in the shape of the circumoral flange, which is conspicuously lobed in P. laeviconchus and unlobed in P. pseudolaeviconchus. Previously, these two species have been confused in the literature under the name P. laeviconchus. A key to Procamallanus (Procamallanus) spp. parasitising freshwater fishes in Africa, including Madagascar, is provided.
Keywords: ryby; hlístice; řeky; Fishes; druhová specificita; Nematoda; Male; Animals; Egypt; Species Specificity; Female; mužské pohlaví; ženské pohlaví; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Rivers; zvířata; Botswana